The Difficulties of Using Capital Letter in Writing Sentences by the Second Year Students of SMKN 1 Tallunglipu in Toraja Utara (LPPM UKI Toraja, 2019)
The objective of the research is find out what are the types of capital letter rules difficulties used by the second year students of SMKN 1 Tallunglipu in writing sentences. This research used quantitative research. It is to find what are the types of capital letter rules difficulties used by the second year students of SMKN 1 Tallunglipu in writing sentences. Thepopulation of this research is the second year students of SMKN 1 Tallunglipu academic year 2018/ / 2019. The total of population is 80 students and taken 30 students through random sampling technique. Based on the data analyzed, the result of this research that the students difficulties of the using capital letter in writing sentences. Severals types of capital letter rules that difficulties used by the second year students of SMKN 1 Tallunglipu in writing sentences are : capitals are used for distinctive historical periods in question number 8 there are 26 students (86,66%) used incorrect answer and question number 7 there are 22 students (73,33%) used incorrect answer, capital are used for many acronyms in question number 10 there are 19 students (63,33%) used incorrect answer, capital are used for calendar items (days) where there are 16 students (53,33%) used incorrect answer.